Communicative influence in english ideation discourse: responsive strategies (based on ted internet platform) - Kaysina, Darya; Кайсіна, Дар'я Михайлівна (ПП "Фенікс", 2018)
Стаття присвячена визначенню та опису респонсивних стратегій, реалізованих суб’єктами англомовного дискурсу ідеації. Англомовний дискурс ідеації є процесом і результатом взаємодії комунікантів у соціально-культурному контексті публічної промови. Суб’єктами цього дискурсу є ідеатор та реципієнт(-и), які здійснюють когнітивно-комунікативну діяльність, змістом якої є прийняття та втілення ідеї, яка є об’єктом цієї взаємодії. Ідея є ментальною структурою, яка втілюється вербальними та невербальними засобами комунікації. Глобальний соціально значущий комунікативний намір ідеатора полягає у здійсненні комунікативного впливу на реципієнтів з метою втілення у соціальну практику ідеї промови. Ця мета досягається через ініціальні комунікативні стратегії інформування, переконування та спонукання, яким підпорядковують- ся субстратегії: інформативні, інформативно-персуазивні, персуазивні, персуазивно-спонукальні і спонукальні. Субстратегії спрямовуються на різні сфери свідомості реципієнтів – раціональне мислення (інформативні, інформативно-персуазивні), емоції (персуазивні), волевиявлення (спонукальні) – або на підсвідомість (персуазивно-спонукальні). Респонсивні комунікативні дії реципієнтів поділяються на миттєві (вербальні: вигуки, короткі відповіді; невербальні: сміх, оплески, жести) і відстрочені (вербальні: кваліфікація ідеаційної промови за допомогою трьох з чотирнадцяти запропонованих прикметників позитивної / негативної оцінки; невербальні: загальна та середньомісячна кількість переглядів відео ідеаційної промови). Наукова цінність дослідження полягає у з’ясуванні конститувних рис нового об’єкта лінгвістичного аналізу – англомовного дискурсу ідеації й з’ясуванні його конститутивних рис із застосуванням інференційного аналізу, який дозволяє виявити стратегії раціонального, емотивного, орієнтованого на волевиявлення комунікативного впливу та відповідних цьому впливу респонсивні стратегії, втілювані у вербальних і невербальних діях суб’єктів дискурсу.

The article focuses on identification and description of the responsive strategies realized by the subjects of English ideation discourse. The term English ideation discourse encompasses a process and result of the communicants’ interaction in the social-cultural context of a public speech. The subjects of such a discourse are the ideator and the recipient(-s) who take part in the cognitive-communicative activity in order to accept and apply the idea that is the object of this interaction. The idea refers to a mental structure translated into verbal and non-verbal means of communication. The ideator’s global socially relevant communicative aim is to exert communicative influence on the recipients, so that they will put the idea into social action. This aim is achieved through the initial communicative strategies of informing, persuading and instructing that govern the sub-strategies: informative, informative-persuasive, persuasive, persuasive-instructive, and instructive. Sub-strategies are aimed at different spheres of the recipients’ consciousness – rational reasoning (informative, informative-persuasive), emotions (persuasive), volition (instructive) or at the subconsciousness (persuasive- instructive). Responsive communicative actions of the recipients are divided into instant (verbal: exclamations, short answers; non-verbal: laughter, applause, gestures) and delayed (verbal: rating an ideation speech by choosing three out of fourteen available adjectives of positive / negative evaluation; non-verbal: general and average monthly number of views of the video recording of an ideation speech). The study is pioneering a systematic cognitive-communicative methodology which reveals constitutive features of a new object of linguistic analysis – English ideation discourse – and provides the tool of inferential analysis to identify and describe rational, emotional, volitional communicative influence with relevant to this influence responsive strategies that are exerted by the subjects of the ideation discourse and are manifested in their verbal and non-verbal actions.
Kaysina, Darya. Communicative influence in english ideation discourse: responsive strategies: based on ted internet platform / D. Kaysina // Одеський лінгвістичний вісник. – 2018. – Вип. 12. – С. 16-23. DOI 10.32837/2312-3192/12/3
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Англомовний дискурс ідеації; волевиявлення; емоції; ініціальна стратегія; комунікативний вплив; раціональне мислення; респонсивна стратегія; Communicative influence; emotions; English ideation discourse; initial strategy; rational reasoning; responsive strategy; volition